The In Situ Expression of IL-6 and IL-1Î² in breast cancer patients - Amal H. Salman; Mayada N. Iqbal; Wasan A. Bakir (College of Pharmacy University of Baghdad, 2017)
Breast cancer is the second most common cancer in women world. Multiple Cytokines appear to have a dominant role in human breast cancer formation. Estimation of the in situ expression of  IL-6 and IL-1Î² in breast cancer patients. A sixty patients with breast cancer BC were divided into two clinical subgroups, (30) with malignant breast cancer MBC and (30) with benign breast tumor as a control group according to histological examination. In situ hybridization technique used for detection of IL-6 and IL-1Î² mRNA sequence in two groups.  The results showed that percentages of mRNA expression of IL-6 and IL-1Î² were in (â‰¥ 11-50%) for malignant breast cancer. This research also investigated that (73.3%) of benign breast tumor were expression less than (<10%) for   IL-6 and IL-1 Î² mRNA. The ISH expression  of the mean percentages of IL-6 and IL-1 Î²   were higher levels in malignant  breast cancer  patients ( 48.13 and 56.07 ,respectively) than benign  tumor (2.73 and 1.40 ,respectively), with highly significantly differences (P<0.01) of  ISH expression for  IL-6  and IL-1 Î² mRNA among two studied groups., the expression   of IL-6 and IL-1 Î² mRNA   are significantly elevated in the tissue of breast cancer patients compared with benign tumor and was found a significant correlation between the expression of IL- 6 and IL-1Î² mRNA in the tissue of breast cancer patients, thus the results of the present study might be explain the pathological role of these two cytokine in breast cancer. Key words: IL-6 mRNA, IL-1Î² mRNA, Breast cancer, ISH.